THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON THE PURCHASE DECISION OF ACER BRAND LAPTOP (Case Study of STIE BINA KARYA Tebing Tinggi Students) - CAHYADI, LUKIETO (Universitas Efarina, 2020)
This study aims to determine